Comparative analysis of number sense performance and problem-solving strategies in gifted and typically developing students - Zübeyde ER; Perihan DİNÇ ARTUT (Humanities & Social Sciences Communications)
Abstract The aim of this study is to examine number sense performance and strategies used by gifted and typically developing students in solving number sense problems. A mixed research method was employed, utilizing an explanatory sequential design. The quantitative research group includes 116 students, with 53 typically developing and 63 gifted students. The qualitative research group consists of a total of 28 students, with 14 students from each group of participants. First, the quantitative group’s performance was assessed with a number sense test. Then, interviews with the qualitative group analyzed their problem-solving strategies. Parametric tests like the t-test analyzed quantitative data, while descriptive analysis examined qualitative data. According to the results of the study, it was observed that the number sense performances of gifted students were at a higher level compared to typically developing students, and gifted students predominantly utilized number sense-based strategies in problem-solving.